Peran Radiologi Dalam Diagnosis Endobronchial Carcinoid Tumor - ICKSAN, AZIZA G. (Indonesian Journal of Cancer, 2014)
Bronchial carcinoid tumors are rare neuroendocrine neoplasma consist of 1â2% of all pulmonary neoplasms and 12â15% of carcinoid tumors in United States. Recently, there is no data in Indonesia. The imaging play important role in diagnosing bronchial carcinoid tumor. This case presentation reported A 35 years old woman with chief complaint of hemoptysis. Acid fast bacilli smear was negative and mantoux test positive. From chest X ray there is a right paracardial consolidation. Chest CT Scan has been done and there was consolidation in right middle lobe with endobronchial mass in intermedius of right bronchial lung. The multidiscipline team diagnosis were endobronchial mass and pulmonary TB. Anti TB treatment had been given. The follow up CT scan after 1 month Anti TB treatment was improvement in consolidation, but the endobronchial mass was stable. She got PET CT Scan and the result was non metabolic nodule. Surgical treatment was done to remove endobronchial mass. The histopathology finding from specimen was typical bronchial carcinoid tumor.